Transição de fase em monocristais de taurina - Freire, Paulo de Tarso Cavalcante (1991)
Taurine, NH3C2H4SO3, is a biological substance found in several organs of human body like retin, liver, heart, muscle, brain and some fluids like milk and bile. Infrared spectrum and Raman spectra were studied at room temperature and identification of normal modes was made. It was also studied the evolution of frequencies and linewidthsof the normal modes from Raman scattering when temperature changed in the range 15K-438K. From these experiments we observed qualitative changes in the Raman spectra. These changes can be understood as a phase transition that occurs between 150K and 200K. This is a transition that shows the characteristics of a second-order transition of the conformational type with C2H4 ions changing their sites from C1 to two non equivalent Ci. It was studied in addition, the dependence of dielectric constant of the crystal with the temperature in the interval 90K to 300K.These measurements showed an anomalous behavior of the dielectric constant curve in the same range of temperature observed by Raman scattering, which confirms the existence of a second-order phase transition in the taurine crystal.